Residents’ quality of life in Smart Tourism Destinations: a theoretical approach - Santos-Júnior, Adalberto (2020)
The objective of this research is to propose a theoretical model based on studies on residents’ quality of life in smart tourism destinations. Smart tourism destinations are territories based on information and communication technologies (ICT), which improve travelers’ tourist experiences as well as affect the quality of life of residents. To know the context of the relationships between tourism and quality of life, main studies and theories regarding these two phenomena are analyzed. Likewise, the relationship between smart places and quality of life is also studied. Therefore, a theoretical model on residents’ quality of life in smart tourism destinations is proposed based on a systematized analysis of the literature. From the theoretical model, it is perceived that residents’ overall life satisfaction results from the relationship between perceived tourism impacts and satisfaction with specific life factors, and they are measured by qualitative indicators. Also, it is identified that the quality of life of residents is clearly influenced by the impacts of tourism and ICTs. In addition, it is understood that the residents’ overall life satisfaction corroborates for the further development of the smart tourism destination. Finally, we understand that the knowledge of residents’ perception and satisfaction of their quality of life contribute to formulation and implementation of urban and tourism development policies in smart tourism destinations.